2023
DOI: 10.1007/s12671-023-02088-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion Mediates the Impact of Family Support on Clinical and Personal Recovery Among People with Mental Illness

Abstract: Objectives The present study aimed to investigate the impact of family support on the recovery of people with mental illness and to explore the potential mechanisms underlying this impact. Specifically, we examined whether family support would be associated with clinical recovery (as indicated by symptom severity, social functioning, and work functioning) and personal recovery (as indicated by recovery perceptions and life satisfaction) among people with mental illness. We also examined whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…Based on data collected from Jews and Arabs in Israel, our results showed that self-compassion mediated the relationship between perceived social support and anxiety. The mediation effect is in line with previous research accenuating the role of self-compassion as a mediator between percieved social support and wellbeing aspects, (Chan, et al, 2023;Wilson et al 2020). This indicates that individuals who are offered greater support through their different social relationships are more likely to be compassionate to themselves and as a result have a more positive wellbeing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on data collected from Jews and Arabs in Israel, our results showed that self-compassion mediated the relationship between perceived social support and anxiety. The mediation effect is in line with previous research accenuating the role of self-compassion as a mediator between percieved social support and wellbeing aspects, (Chan, et al, 2023;Wilson et al 2020). This indicates that individuals who are offered greater support through their different social relationships are more likely to be compassionate to themselves and as a result have a more positive wellbeing.…”
Section: Discussionsupporting
confidence: 89%
“…Wilson, Weiss & Shook, (2020) found that self -compassion was one of three factors that accounted for perceived social support and psychological wellbeing outcomes. Similarly, Chan, Yip & Tsui, (2023), investigated the impact of family support on the recovery of people with mental illness and explored the potential mechanisms underlying this impact. They found positive associations between family support and self-compassion.…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores indicated higher levels of clinical recovery. This measure had good validity and reliability in past studies (Chan et al, 2023). Its Cronbach’s α was 0.91 in this study.…”
Section: Methodsmentioning
confidence: 74%
“…Existing evidence suggests that various factors contribute to promoting personal recovery among individuals with mental illness. For example, strong family support has been associated with a sense of being on the path to recovery, as it influences feelings of happiness and fulfillment in life (Chan et al, 2023 ; Kaewprom et al, 2011 ). Additionally, community attitudes toward mental health are crucial in helping individuals overcome stigma and regain control over their lives (Chan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%